A gain of function variant in RGS18 candidate for a familial mild bleeding syndrome - Vayne, Caroline; Roux, Maguelonne; Gruel, Yves; Poggi, Marjorie; Pouplard, Claire; Peiretti, Franck; Trégouët, David-Alexandre; Nurden, Paquita; Alessi, Marie-Christine (Journal of thrombosis and haemostasis, 2025)
Inherited platelet diseases are bleeding disorders characterized by either defects in platelet count or platelet function, the latter being less common and very heterogeneous. Numerous gene variants associated with abnormal receptors, granules, and signaling pathways have been reported. Despite significant advancements in our understanding, many patients still lack a precise diagnosis. To identify the genetic basis of a novel mild bleeding syndrome in a family exhibiting a selective defect of platelet aggregation. Our study included 6 family members across 3 generations who displayed reduced platelet aggregation in response to adenosine diphosphate, protease-activated receptor 1-activating peptide, arachidonic acid, and epinephrine but not collagen. Platelet morphology, granule content, and expression of major surface glycoproteins were all found to be normal. Whole exome sequencing was performed for affected and nonaffected family members. We identified RGS18, which encodes the regulator of G protein signaling (RGS) 18, as a candidate gene for the platelet function defect observed in this family. The RGS18 protein serves as a crucial negative regulator of G protein-coupled receptor signaling and coordinates the signaling pathways of natural platelet inhibitors. The heterozygous RGS18 c.643C>T, p.Arg215∗ variant was found to cosegregate among all 6 affected subjects. Truncation at Arg215 removes the S216 and S218 phosphorylation sites, which are crucial regulatory domains for RGS18 activation. The impaired platelet function is thought to arise from excessive platelet downregulation due to constitutive activation of RGS18, resulting from a loss of association of the truncated form with the 14-3-3 protein.